ANALISIS PENETAPAN KAWASAN ANDALAN DI KABUPATEN LAHAT - Fachrizal Bacri (Department of Development Economics, Universitas Sriwijaya, 2005)
In order to implement Undang-Undang No. 22 and Undang-Undang N0. 25 Tahun 1999 in Lahat Regency, we propose other approach of regional planning. Per capita income, subsector of economic base sector and regional specialization index were significant indicators to choose prime mover of potential economics locations in district level. finding of the research, there were only two prime mover of potential economics districts in Lahat regency, Tanjung Sakti regency, and Kota Agung regency.KeyWords: Locationt Quotient, Economic Base, Klassen Typology, Regional Specialization Index.